RAGE and its ligand amyloid beta promote retinal ganglion cell loss following ischemia-reperfusion injury - Seyed Hosseini Fin, Nafiseh; Georgevsky, Dana; Sukkar, Maria B.; Golzan, S. Mojtaba (Frontiers in Cellular Neuroscience, 2023)
Glaucoma is a progressive neurodegenerative disease associated with age. Accumulation of amyloid-beta (Aß) proteins in the ganglion cell layer (GCL) and subsequent retinal ganglion cell (RGC) loss is an established pathological hallmark of the disease. The mechanism through which Aß provokes RGC loss remains unclear. The receptor for the advanced glycation end product (RAGE), and its ligand Aß, have been shown to mediate neuronal loss via internalizing Aß within the neurons. In this study, we investigated whether the RAGE–Aß axis plays a role in RGC loss in experimental glaucoma. Retinal ischemia was induced by an acute elevation of intraocular pressure in RAGE–/– and wild-type (WT) control mice. In a subset of animals, oligomeric Aß was injected directly into the vitreous of both strains. RGC loss was assessed using histology and biochemical assays. Baseline and terminal positive scotopic threshold (pSTR) were also recorded. Retinal ischemia resulted in 1.9-fold higher RGC loss in WT mice compared to RAGE–/– mice (36±3% p<0.0001 vs. 19±2%, p=0.004). Intravitreal injection of oligomeric Aß resulted in 2.3-fold greater RGC loss in WT mice compared to RAGE–/– mice, 7-days post-injection (55±4% p=0.008 vs. 24±2%, p=0.02). We also found a significant decline in the positive scotopic threshold response (pSTR) amplitude of WT mice compared to RAGE–/– (36±3% vs. 16±6%). Collectively, RAGE–/– mice are protected against RGC loss following retinal ischemia. Intravitreal injection of oligomeric Aß accelerated RGC loss in WT mice and not RAGE–/–. A co-localization of RAGE and Aß, suggests that RAGE–Aß binding may contribute to RGC loss.